Iconographic program of the oldest wall paintings in the church of the virgin Peribleptos at Ohrid: A list of frescoes and notes on certain program particularities - Marković Miodrag (Zograf, 2011)
The thematic repertoire of frescoes in the Church of the Virgin Peribleptos in Ohrid is presented systematically and in detail. The list of representations includes a number of scenes and individual figures of saints who were not identified earlier on, or were incorrectly identified. In addition to that, the inscriptions on the scrolls of saints in the naos and narthex have been published, as well as the ktetor’s inscription and the inscriptions written in acronymic form beside the apotropaic crosses. The paper also deals with some features of the iconographic program.